Extraction of copper from aqueous sulfate medium using microcapsule coated with cyanex 301 - Yeoh, Choon Nai
The copper extraction with the microcapsules containing Cyanex 301 which prepared by solvent evaporation method was study. Gum arabic as dispersion stabilizer and dichloromethane as solvent are used in microcapsules preparation. Gum arabic shows a good formability of microcapsules than gelatin does. The effect of sulfuric acid (H2SO4) molarity, temperature, and amount of microcapsules in copper extraction were investigated.